Ministry of Transportation (MOT) / Mohamad Syafiq Mohammad ... [et al.] - Mohammad, Mohamad Syafiq; Mohmad Omar, Muhammad Hilman; Mohd Yusak, Nor Emyzan; Shuhada Azil, Nurul Ain; Mustaffa, Musfirah (Universiti Teknologi Mara, Perak, 2016)
Ministry of Transportation is a government office building that located at Wilayah Persekutuan Putrajaya. The building is occupied by Ministry of Transportation department itself with a Jabatan Pengangkutan Jalan (JPJ). The Ministry of Transport is a ministry of the Government of Malaysia that is responsible for transport, road transport, civil aviation, marine, road safety, port authority, railway assets, maritime, air accident investigation, logistic, maritime safety, shipping, rail transport, airport, airline. The Minister of Transport administers his functions through the Ministry of Transport and a range of other government agencies. The current Minister of Transport is Datuk Seri Liow Tiong Lai, whose term began on 27 June 2014. In the term of the building design, the architecture has been design in a shape of triangle with the concept of modern design. It will provide a nature lighting to any space or corner from any direction due to the sun movement. By this invention, it will be a benefit to the owner as the cost of electricity for the interior lighting will be reduce during the daylight. Our building (MOT) is modern building that was located at Putrajaya has their specialist for government commercial building. The major material in building Ministry of Transportation is glass window. They have cleaning maintenance for glass window in every three weeks. There are also can manage their electrical bil because they can use energy sever. Cause the window glassed can absorb the sunlight lighting to permit that light come in commercial building (MOT). Ministry of Transportation building also can save their energy with their employee habit that is when lunch hours they have close some light in employee place because not many occupants at that place so can release some energy. Maintenance team at Ministry of Transportation also give an important role about the energy saver because maintenance team can manage use of energy in air conditional system, electrical system and services system. For air conditional system, if some place that no have many occupant and after office hour maintenance team will reduce the energy of air conditional with close some air handling unit (AHU) for energy saver. Then, for electrical saver, maintenance team will close some elevator after office hour or weekend days. Last but not lease for services, maintenance team will close some main pipe at some floor to reduce use of water because maybe have some leaking pipe on toilet or mosque. Ministry of Transportation also give a very good facility to their employee and customer because Ministry of Transportation building have many space for parking for example at basement B1, B2, B3 and B4 have four storey for parking space and beside the Ministry of Transportation also have parking at least 50 lot have provided for parking space. For parking facilities at Ministry of Transportation building at beside building is free of charge for everyone and in basement parking at Ministry of Transportation is for employee at Ministry of Transportation for example Jabatan Pengangkutan Jalan (JPJ). Lastly, Ministry of Transport have unique shape of design because Ministry of Transportation building have oblong shape. That shape can reduce wind pressure on the structure of the building because that shape like have aerodynamic style on this shape not only reduce wind pressure that also can comfortable occupant on the building from shaking.